Spatial Distribution of Mantis Shrimp (Harpiosquilla raphidea) in Small-Scale Gillnet Fishery: A Case Study in Kuala Tungkal, Tanjung Jabung Barat Regency, Jambi - Farhan Ramdhani; Septy Heltria; Ester Restiana Endang Gelis; Nofrizal Nofrizal; Romie Jhonnerie; Irfan Zidni (Jurnal Kelautan Tropis, 2023)
Mantis Shrimp is one of economically important species due to its high value for export commodities. Mantis shrimp fishing in Kuala Tungkal is categorized as small-scale fisheries. This study aims to investigate the spatial distribution of mantis shrimp catches, both the number (individuals) and body length (BL) (cm) based on the distance from the shoreline to the fishing ground. A survey method was conducted in Kuala Tungkal, Tanjung Jabung Barat Regency, Jambi Province in December 2018. The observation covered 23 fishing trips by gillnet within 437 km2. The results revealed that the spatial distribution of the average number (individuals) of mantis shrimp in various stratifications reached 28-31 individuals. However, the farther fishing ground with higher salinity levels obtained a larger average size of mantis shrimp body length (BL). In the 0-4 mile stratification, it was found that the average catch size is 17.3 cm under the first maturity size which should be 19 cm. Meanwhile, in average the observed water condition as follow temperature is 28.2oC, DO = 7.4 mg/L, pH = 7, brightness = 1.1 m, and salinity is 20.9 ppt. At the end, the result of this spatial distribution may become an input for coastal resource management strategies and can support sustainable mantis shrimp fishing efforts.